Lithium metal protective layer for sulfide solid-state battery as well as preparation method and application of lithium metal protective layer
Through technical means such as high-energy ball milling and high-temperature pressing, a lithium metal protective layer for sulfide solid-state batteries was prepared, which solved the problem of interface instability between lithium metal and sulfide electrolyte, and significantly improved the battery's cycle stability and lithium ion transmission performance.
Patent Information
- Application Number
- CN202411969905.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the prior art, the interface between lithium metal and sulfide electrolyte has a high degree of instability, resulting in problems such as decreasing battery efficiency, rapid capacity attenuation, and short-circuiting of battery cells.
Silicon and non-lithium metal oxides are used as raw materials, and the premix effect is achieved in the preliminary reaction through high-energy ball milling. The binder is added and rolled through a roller press, and finally the high-temperature press is carried out to prepare a lithium metal protective layer containing silicon oxide and metal element, which is closely adhered to the surface of the lithium metal negative electrode.
The film forming properties of the lithium metal protective layer and the cycling stability of the battery are improved, the growth and interface side reactions of lithium dendrites are inhibited, the lithium ion transmission performance is enhanced, the volume expansion is alleviated, and the specific capacity and Coulomb efficiency of the battery are improved.
Smart Images

Figure CN119764762A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and in particular to a lithium metal protective layer for a sulfide solid-state battery, and a preparation method and application thereof. Background Art
[0002] With the advancement of science and technology, the existing liquid lithium-ion batteries cannot meet social needs, and their flammable and explosive properties make society urgently need a low-carbon, environmentally friendly, efficient and safe new energy system. Based on the huge potential of solid-state batteries in energy density, safety and cycle life, all-solid-state lithium batteries use solid electrolytes instead of liquid electrolytes, which has become the most important development direction of lithium batteries recognized in the international energy field.
[0003] Sulfide electrolytes have high lithium ion conductivity and excellent mechanical properties, and are recognized as promising material systems for commercializing solid-state batteries. Although the currently successfully commercialized graphite anode has the advantages of low cost and high stability, its low theoretical capacity can no longer meet today's energy needs. Lithium metal has become a current research hotspot due to its low oxidation potential and high theoretical capacity. However, the activity of lithium metal makes the interface with the sulfide electrolyte highly unstable, resulting in problems such as decreased coulombic efficiency of the battery, rapid capacity decay, and battery short circuit, which is mainly attributed to lithium dendrite growth, severe interfacial side reactions, and huge volume expansion. At high current density, the stripping rate of lithium will be greater than the deposition rate, resulting in voids. A large number of electrons will accumulate at the tip of the void, inducing lithium ion deposition, thereby generating lithium dendrites, which will further deteriorate and eventually penetrate the electrolyte, causing the battery to short-circuit. In addition, the sulfide electrolyte reacts with lithium metal to form a passivation layer at the interface. Ideally, the passivation layer will inhibit interfacial side reactions and lithium dendrite growth. However, the composition of the interface layer is relatively complex, and the thickness is usually too large, which leads to a significant increase in the internal resistance of the battery and a decrease in performance. At present, people mainly optimize solid-state lithium metal batteries by introducing artificial protective layers, lithium metal pretreatment and lithium metal substitution to address the above problems.
[0004] Introducing an artificial protective layer is currently a relatively simple and quick method for protecting lithium metal. However, the introduced protective layer faces problems such as low conductivity and reduced battery capacity, and mechanical and physical properties must also be considered. In the prior art, there are protective layers prepared using silicon oxide, metal elements, etc. as raw materials. Although it protects the lithium metal negative electrode to a certain extent, due to the poor film-forming properties of silicon oxide and metal elements after mixing, the battery's cycle stability is low.
[0005] Therefore, there is an urgent need for a protective layer that takes into account both cycle stability and protection of the lithium metal negative electrode. Summary of the invention
[0006] In view of the defects in the prior art, the purpose of the present invention is to provide a lithium metal protective layer for sulfide solid-state batteries and a preparation method and application thereof. The present invention uses silicon and non-lithium metal oxide as raw materials, converts mechanical energy into chemical energy through high-energy ball milling, and performs a preliminary reaction while ensuring that the raw materials are fully mixed, so that the mixed powder (Si-M x O y , M is a metal element) to produce a pre-mixing effect, which is beneficial to improving the film-forming property of the mixed powder, and then adding a binder to further improve the film-forming property of the mixed powder, synergistically improving the cycle stability of the battery; the mixed powder is then rolled on a roller press to prepare a large-area protective film, which is beneficial to adapt to solid-state batteries of various sizes; finally, the protective film is pressed at high temperature to promote the complete reaction of the mixed powder to generate a lithium metal protective layer containing silicon oxide and metal elements, and make it closely adhere to the surface of the lithium metal negative electrode, so as to avoid the lithium metal from losing contact with the protective layer when a huge volume expansion occurs during the battery cycle, thereby increasing the battery impedance and reducing the stability.
[0007] The purpose of the present invention can be achieved by the following scheme:
[0008] In a first aspect, the present invention provides a method for preparing a lithium metal protective layer for a sulfide solid-state battery, comprising the following steps:
[0009] S1. Under an inert gas, silicon and metal oxide are subjected to high-energy ball milling to obtain a mixed powder;
[0010] S2, adding a binder to the mixed powder and rolling to obtain a protective film;
[0011] S3, pressing the protective film onto the surface of the lithium metal sheet at high temperature to obtain a lithium metal protective layer.
[0012] As an embodiment of the present invention, in step S1, the silicon includes one or more of nano-scale silicon powder and micron-scale silicon powder.
[0013] As an embodiment of the present invention, in step S1, the metal oxide includes one or more of silver oxide, tin oxide, magnesium oxide, and aluminum oxide. Preferably, the metal oxide is magnesium oxide.
[0014] As an embodiment of the present invention, in step S1, the mass ratio of silicon to metal oxide is 0.4 to 2:1. Since the chemical reaction itself is incomplete, a small amount of Si and metal oxides remain in the protective layer. These substances will be evenly dispersed inside the protective layer, and continue to react during the battery cycle, thereby replenishing the main components missing in the protective layer. If there is an excess of silicon powder, it may lead to incomplete reaction, causing the remaining silicon to form Li-Si alloy with lithium metal, but the Li-Si alloy will cause a large volume change in the protective layer, so it is necessary to select a suitable ratio.
[0015] As an embodiment of the present invention, in step S1, the ball-to-material ratio of the high-energy ball milling is 20-50:1, the rotation speed is 200-500 rpm, and the time of the high-energy ball milling is 4-10 hours.
[0016] The high-energy ball mill of the present invention is based on the fact that the centrifugal force generated by ordinary ball milling after exceeding a certain rotation speed will exceed the gravity on the grinding balls. At this time, the grinding balls and the ball mill jar move simultaneously, which can easily lead to grinding failure. The high-energy ball milling can promote the balance of multiple forces, maintain effective grinding, and can prepare a large amount of protective layer precursors.
[0017] In some embodiments, the inert gas is argon.
[0018] As an embodiment of the present invention, in step S2, the binder includes one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), and polyacrylonitrile (PMA).
[0019] As an embodiment of the present invention, in step S2, the amount of the binder used is 0.5-3% of the weight of the mixed powder. In some embodiments, the mixed powder is ground after the binder is added, and the grinding time is 0.5-2h.
[0020] As an embodiment of the present invention, in step S2, the rolling is performed multiple times using a roller press. In the present invention, because silicon itself has a large volume change, reducing its particle size can effectively inhibit its volume expansion. By adding a binder and rolling with a roller press, a large-area protective layer can be prepared to adapt to solid-state batteries of various sizes. At the same time, after mechanical pressing, the protective layer has a dense porous structure, which is beneficial to improve Li + Transmission and relief of volume expansion.
[0021] As an embodiment of the present invention, in step S2, the high temperature pressing pressure is 300 MPa to 400 MPa, the high temperature pressing temperature is 160 to 180° C., and the holding time is 15 to 20 min.
[0022] Furthermore, the high-temperature pressing process includes: placing a protective layer on the lithium metal (negative electrode sheet), then placing it in a tablet pressing mold, heating the upper and lower stainless steels of the mold to a specified temperature, and pressing it into a lithium metal protective layer.
[0023] In a second aspect, the present invention provides a lithium metal protective layer obtained by the preparation method.
[0024] In a third aspect, the present invention provides an application of the lithium metal protective layer in the preparation of a sulfide all-solid-state battery.
[0025] As an embodiment of the present invention, the sulfide all-solid-state battery includes a lithium metal sheet, a lithium metal protective layer, a sulfide solid electrolyte, and a ternary material composite positive electrode sheet arranged in sequence.
[0026] Furthermore, the sulfide solid electrolyte includes Li2S-P2S5, Li7P3S 11 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 、Li6PS5Br、Li6PS5I、Li 11 Si2PS 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl, Li 10 SnP2S 12 , Li 10 GeP2S 12 One or more of .
[0027] Furthermore, the ternary material composite positive electrode plate includes a positive electrode active material, a sulfide electrolyte, and a conductive agent; the positive electrode active material includes one or more of NCM111, NCM424, NCM523, NCM622, and NCM811; the sulfide electrolyte is a hard sulfide electrolyte with added metal elements. The battery is pressed into an all-solid-state battery in the order of positive electrode-electrolyte-negative electrode. The battery effectively improves safety, interface resistance, capacity, cyclability, and rate capabilities.
[0028] The traditional method of directly mixing silicon oxide and non-lithium metal elements will result in poor film-forming properties of the mixed powder, affecting the cycle stability of the battery. Even if silicon oxide and non-lithium metal elements are mixed by high-energy ball milling, the pre-mixing effect of the present invention cannot be achieved, and the improvement of film-forming properties is limited. The present invention does not directly use silicon oxide and non-lithium metal elements as raw materials, but creatively performs high-energy ball milling on silicon and metal oxides to achieve a pre-mixing effect in the initial reaction, thereby improving the subsequent film-forming properties and further improving the cycle life of the battery.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The protective layer prepared by the present invention is mainly composed of silicon oxide and non-lithium metal single substance. Silicon oxide has high stability with sulfide electrolyte, so that the protective layer can isolate the lithium metal negative electrode from the sulfide electrolyte, so that the two will not have side reactions, inhibit the growth of lithium dendrites, thereby improving the battery specific capacity and coulomb efficiency, and silicon oxide and non-lithium metal single substances are relatively stable. In addition, during the battery cycle, the non-lithium metal single substance in the protective layer will form an alloy with lithium, improve the conductivity in the protective layer, reduce the battery impedance, and help improve the battery cycle stability, thereby avoiding the problem of high interface impedance of the protective layer due to the low conductivity of silicon oxide.
[0031] 2. The present invention creatively utilizes high-energy ball milling to cause a preliminary reaction while ensuring that the raw materials (silicon and non-lithium metal oxides) are fully mixed, so that the mixed powder obtained by the preliminary reaction produces a pre-mixing effect, which is beneficial to improving the film-forming property of the mixed powder. The binder is then added to further enhance the film-forming property of the mixed powder, thereby synergistically enhancing the cycle stability of the battery.
[0032] 3. The binder added in the present invention can also improve the ductility of the mixed powder and prepare a large-area protective film, which is conducive to adapting to solid-state batteries of various sizes.
[0033] 4. The present invention promotes the complete reaction of the mixed powder to generate a lithium metal protective layer containing silicon oxide and metal elements through high-temperature pressing, and makes it closely adhere to the surface of the lithium metal negative electrode, so as to prevent the lithium metal from losing contact with the protective layer when the lithium metal undergoes a huge volume expansion during the battery cycle (volume expansion during lithium insertion / extraction), thereby increasing the battery impedance and reducing the stability. In addition, the pressed protective layer has a porous structure, which not only has better lithium ion transmission performance than the traditional protective layer, but also the pores inside the protective layer can effectively alleviate the volume expansion of the protective layer.
[0034] 5. The protective layer of the present invention has the advantages of excellent initial charge and discharge efficiency, stability with sulfide electrolyte, low volume change, high film-forming property and ductility, and can cope with lithium metal sheets of different sizes; at the same time, the preparation process is simple and fast, and can be prepared on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0036] Figure 1 This is a microscopic morphology of the lithium metal protective layer in Example 1. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0038] The components of the nano-scale silicon powder or micron-scale silicon powder used in the present embodiment and the comparative example are all simple silicon.
[0039] Example 1
[0040] In an argon-filled glove box, place about 0.2g of nano-silicon powder and 0.35g of silver oxide in a zirconium oxide ball mill, add about 16.5g of ball mill beads, seal the ball mill well with tape, move out of the glove box, and perform high-energy ball milling for 4 hours at a speed of 450 rpm. Place the mixed powder after ball milling in a glove box. Weigh 500mg of the above powder, add 1% PTFE to it, grind it for 1 hour to make it fully mixed and have a certain film-forming property. Then put it into a roller press and roll it several times to make the powder into a film of uniform thickness. Use a 10mm punch to cut the disc, and put it into a 10mm stainless steel tablet pressing mold together with a lithium metal sheet of the same size for high-temperature pressing. When the stainless steel is heated to 160°C, it is pressed into sheets. After demolding, a sheet consisting of a lithium metal sheet and a protective layer (microscopic morphology such as Figure 1 As shown, a lithium metal negative electrode sheet composed of a porous structure) was pressed at a pressure of 300Mpa for 15 minutes. 10mg of the composite positive electrode (70% NCM811-29% Li6PS5Cl-1% VGCF) (all of the above are mass ratios) was uniformly pressed on the surface of 100mg of Li6PS5Cl electrolyte at a pressing pressure of 300Mpa and demolded. The composite positive electrode / sulfide electrolyte / lithium metal negative electrode sheet was assembled in a pressure battery to obtain a sulfide all-solid-state battery.
[0041] Example 2
[0042] The difference between this embodiment and embodiment 1 is that silver oxide is replaced by tin oxide.
[0043] The specific method is: in a glove box also filled with argon, prepare a sulfide all-solid-state battery according to the method in Example 1.
[0044] Example 3
[0045] The difference between this embodiment and embodiment 1 is that silver oxide is replaced by magnesium oxide.
[0046] The specific method is: in a glove box also filled with argon, prepare a sulfide all-solid-state battery according to the method in Example 1.
[0047] Example 4
[0048] The difference between this embodiment and embodiment 1 is that silver oxide is replaced by aluminum oxide.
[0049] The specific method is: in a glove box also filled with argon, prepare a sulfide all-solid-state battery according to the method in Example 1.
[0050] Example 5
[0051] The preparation method of this embodiment is basically the same as that of Example 1, except that the ball milling time is replaced from 4 h to 10 h, the high-temperature pressing temperature is replaced from 160° C. to 180° C., and the holding time is replaced from 15 min to 20 min to prepare a sulfide all-solid-state battery.
[0052] Comparative Example 1
[0053] The difference between this comparative example and Example 1 is that the protective layer is not added.
[0054] The specific method is: in a glove box also filled with argon, prepare a sulfide all-solid-state battery according to the method in Example 1.
[0055] Comparative Example 2
[0056] The difference between this comparative example and Example 1 is that no binder is added.
[0057] The specific method is: in a glove box also filled with argon, silicon powder and metal oxide are mixed according to the method in Example 1, and then a sulfide all-solid-state battery is prepared according to the method in Example 1.
[0058] Comparative Example 3
[0059] The difference between this comparison and Example 1 is that the effect of adding metal oxide is not achieved.
[0060] The specific method is: in a glove box also filled with argon, grind silicon and a binder, and then prepare a sulfide all-solid-state battery according to the method in Example 1.
[0061] Comparative Example 4
[0062] The difference between this comparison and Example 1 is that the effect of silicon is not added.
[0063] The specific method is: in a glove box also filled with argon, the metal oxide and the binder are mixed according to the method in Example 1, and then the sulfide all-solid-state battery is prepared according to the method in Example 1.
[0064] Comparative Example 5
[0065] The preparation method of this comparative example is basically the same as that of Example 1, except that high-energy ball milling is replaced by ordinary mixing; wherein the ordinary mixing is carried out using a powder mixer to prepare a sulfide all-solid-state battery.
[0066] Comparative Example 6
[0067] The preparation method of this comparative example is basically the same as that of Example 1, except that the time of high-energy ball milling is replaced with 2 hours to prepare a sulfide all-solid-state battery.
[0068] Comparative Example 7
[0069] The preparation method of this comparative example is basically the same as that of Example 1, except that the temperature of high-temperature pressing is replaced with 100° C. and the holding time is 8 min.
[0070] Performance Testing
[0071] First efficiency: The all-solid-state battery was tested using the Xinwei battery testing system (model: CT-4000). The 0.1C / 0.1C charge and discharge process was used to test the first charge and discharge capacity of the solid-state lithium battery. The first efficiency (%) = first discharge capacity / first charge capacity × 100%.
[0072] Cycling stability of the whole battery: The all-solid-state battery was tested using the Xinwei battery testing system, equipment model: CT-4000, using a 0.5C / 0.5C charge and discharge process to test the capacity retention rate after the cycle. Capacity retention rate % = 100 cycles of discharge capacity / first discharge capacity × 100%.
[0073] Table 1 Performance test results of Examples 1-5 and Comparative Examples 1-7
[0074]
[0075] From the test results in Table 1, it can be seen that the sulfide all-solid-state batteries of Examples 1-4 have high initial charge and discharge specific capacity and efficiency, and good cycle stability under high current. Silicon provides the battery with a higher capacity while stabilizing the interface between the negative electrode and the electrolyte; forming an SEI layer with SiO2 and Li2O as the main components, effectively inhibiting the growth of lithium dendrites and improving the stability of the battery; the addition of a binder increases the lithium ion conductivity of the protective layer and reduces the interface impedance. Among them, Example 3 has the highest specific capacity and capacity retention rate, indicating that when the metal oxide is magnesium oxide, the protection effect on the lithium metal negative electrode is the best. Example 5 increases the ball milling time, high temperature pressing temperature and holding time, further improving the initial effect on the lithium metal negative electrode.
[0076] In Comparative Example 1, no protective layer was added, and lithium dendrites grew and penetrated the electrolyte, causing a short circuit in the battery.
[0077] In Comparative Example 2, no binder is added, the conductivity of the protective layer is low, and the interface impedance is large, which is not conducive to battery discharge and makes the battery stability worse.
[0078] In Comparative Example 3, no metal oxide is added. Although silicon provides a high capacity battery, the volume expansion of silicon and the penetration of lithium dendrites deteriorate the battery stability. This is because an effective SEI layer is not formed.
[0079] In Comparative Example 4, silicon is not added. Although the battery has good stability, the metal oxide itself has a low capacity and most of the lithium metal reacts with the metal oxide, causing the battery capacity to be greatly reduced. At a high rate, the specific capacity is less than 100 mAh / g, and the high capacity of the all-solid-state battery cannot be achieved.
[0080] Comparative Example 5 simply mixed the powders without sufficient kinetic energy to react, resulting in low initial effect and severe capacity decay. Similarly, Comparative Example 6, despite high-energy ball milling, had a slight improvement over Comparative Example 5, but the time was insufficient, the reaction was not complete, the capacity was low, and the life was short.
[0081] Comparative Example 7 shortens the pressing temperature and time. Although high-energy ball milling is performed, the pressing temperature and time are insufficient, and the protective layer still contains a large amount of silicon and metal oxides, which are not conducive to lithium ion transmission, resulting in low capacity and severe attenuation.
[0082] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a lithium metal protective layer for a sulfide solid-state battery, characterized in that: The following steps are involved: S1. Under an inert gas, silicon and metal oxide are subjected to high-energy ball milling to obtain a mixed powder; S2, adding a binder to the mixed powder and rolling to obtain a protective film; S3, pressing the protective film onto the surface of the lithium metal sheet at high temperature to obtain a lithium metal protective layer.
2. The preparation method according to claim 1, characterized in that: In step S1, the silicon includes one or more of nano-scale silicon powder and micro-scale silicon powder.
3. The preparation method according to claim 1, characterized in that: In step S1, the metal oxide includes one or more of silver oxide, tin oxide, magnesium oxide, and aluminum oxide.
4. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of silicon to metal oxide is 0.4-2:
1.
5. The preparation method according to claim 1, characterized in that: In step S1, the ball-to-material ratio of the high-energy ball milling is 20-50:1, the rotation speed is 200-500 rpm, and the high-energy ball milling time is 4-10 hours.
6. The preparation method according to claim 1, characterized in that: In step S2, the binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, and polyacrylonitrile.
7. The preparation method according to claim 1, characterized in that: In step S2, the amount of the binder used is 0.5-3% of the weight of the mixed powder.
8. The preparation method according to claim 1, characterized in that: In step S2, the pressure of the high temperature pressing is 300MPa-400MPa; the temperature of the high temperature pressing is 160-180°C, and the holding time is 15-20min.
9. A lithium metal protective layer obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the lithium metal protective layer as claimed in claim 9 in the preparation of sulfide all-solid-state batteries.
Citation Information
Patent Citations
Lithium metal negative electrode and preparation method and application thereof
CN118676374A
Apparatus for measuring thickness of material using x-ray
KR1020190113562A
Negative electrode material for lithium ion battery and preparation method therefor
WO2018113267A1
KR20230027418A